Bimaxillary Osteotomy for Jaw Deformity With Facioscapulohumeral Muscular Dystrophy. Issue 3 (May 2016) - Kawasaki, Takako; Ohba, Seigo; Fujimura, Yuji; Asahina, Izumi
Abstract : Abstract: Facioscapulohumeral muscular dystrophy (FSHD) is a subtype of muscular dystrophies which reduces the muscle strength, especially the regions of scapular, shoulder, and upper arms, progressively. According to progressive muscle weakness in FSHD, postoperative stability of patient with FSHD after orthognathic surgery is not reliably acquired same as healthy subjects. A 32-year-old woman with FSHD underwent orthodontic and orthognathic surgical treatment due to jaw deformity. She has been followed up more than 3 years after surgery and acquired skeletal stability. This patient is the first report that showed long-term skeletal stability after orthognathic surgery in patient with FSHD. This patient report suggests that it is possible to apply orthognathic surgical treatment to patients with FSHD.